The Factors Affecting Consumers Pay with Go-Pay on Go-Jek - Bagudek Tumanggor; Vitryani Tarigan (Budapest International Research and Critics University, 2020)
This study aims to examine and find out more clearly how the factors that influence consumers pay with Go-pay on Go-jek. As for the problem that the author raised, namely: How does the influence of easy payment of the use of GO-PAY to the interests of GO-JEK customers?This study uses a quantitative method that involves 50 respondents. Data collection is done by using questionnaires. The data obtained were analyzed using a statistical formula, i.e. using multiple regression analysis whose processing was carried out with the SPSS Version 23 program.Quantitative analysis results show that the variable ease of payment and price cuts significantly influence the use of Go-pay. Based on the results of the study, the hypothesis was accepted stating that there was a significant influence between the ease of payment and price cuts on the use of Go-pay on consumers at the Faculty of Economics, Universitas Simalungun, Pematangsiantar.